(untitled) (Bangladesh Journal of Medicine, 2016)
Renal tubular acidosis (RTA) is a constellation of syndromes arising from different derangements of tubular acid transport. Multiple associations have been established with renal tubular acidosis. We report a case of distal renal tubular acidosis which may be associated with undifferentiated connective tissue disease in which patient is also having autoimmune hypothyroidism along with that is not very common. Bangladesh J Medicine Jan 2016; 27(1) : 37-39